Clinical and surgical management of pheochromocytomas and paragangliomas - de Miguel, Valeria; Cuffaro, Paula; Medici , Juan; Cavadas, Demetrio (Revista del Hospital Italiano de Buenos Aires, 2015)
Pheochromocytomas and paragangliomas are rare neuroendocrine tumors with different clinical manifestation associated with high morbidity and mortality. Recognize signs and symptoms is the first step in diagnosis. Urinary fractionated metanephrines have an excellent specificity and sensitivity. Computed Tomography (CT) is the first-choice imaging modality for location. F18-DG positron tomography (PET)/CT scanning is the functional modality of choice for metastatic disease. Surgery is the only curative treatment. Minimally invasive adrenalectomy is the surgical approach for most adrenal pheochromocytomas. Perioperative alpha and beta blockade for 7 to 14 days normalize blood pressure and prevent perioperative cardiovascular complications. Is recognize that at least one-third of the patients have disease-causing germline mutations. Genetic testing must be orientated to syndromic features, presentation, localization and biochemical profile of these tumors. Multidisciplinary teams at centers with appropriate expertise are recommended to ensure a favorable outcome
Keywords: pheochromocytoma; paraganglioma; neuroendocrina tumors; hypertension; incidentaloma; catecholamines; metanephrines; adrenalectomy; malignancy; genetics